Colloidal suspensions of highly luminescent lanthanide-based coordination polymer molecular alloys for ink-jet printing and tagging of technical liquids. Issue 8 (5th March 2021) - Pointel, Youenn; Daiguebonne, Carole; Suffren, Yan; Le Natur, Francois; Freslon, Stéphane; Calvez, Guillaume; Bernot, Kevin; Jacob, David; Guillou, Olivier
Abstract : A series of lanthanide-based coordination polymer molecular alloy colloidal dispersions usable for ink-jet printing and tagging of technical liquids. Abstract : Highly luminescent and color-tunable stable colloidal suspensions of molecular alloys are reported. They are produced via a green synthetic route in ethanol medium. The mean hydrodynamic diameter of the colloids is about 140 nm and the colloidal suspensions are stable for more than a month. The optical properties of the molecular alloy suspensions and their bulk counterparts are extremely similar. To the best of our knowledge, this series of suspensions constitutes the first example of hetero-lanthanide coordination polymer molecular alloy (LnCPMA)-based colloidal suspensions with sizeable luminescence intensity and a wide range of accessible colors. This high color tunability paves the road toward tagging of technical liquids. We also demonstrate that they can be used in ink-jet printers for luminescent anti-counterfeiting tagging.